2020
DOI: 10.1161/circulationaha.120.046928
|View full text |Cite|
|
Sign up to set email alerts
|

Cangrelor, Tirofiban, and Chewed or Standard Prasugrel Regimens in Patients With ST-Segment–Elevation Myocardial Infarction

Abstract: Background: Standard administration of newer oral P2Y 12 inhibitors, including prasugrel or ticagrelor, provides suboptimal early inhibition of platelet aggregation (IPA) in ST-segment elevation myocardial infarction (STEMI) patients undergoing primary percutaneous coronary intervention (PCI). We sought to investigate the effects of cangrelor, tirofiban and prasugrel, administered as chewed or integral loading dose, on IPA in patients undergoing primary PCI. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(41 citation statements)
references
References 40 publications
1
40
0
Order By: Relevance
“…The identification of the mechanisms leading to the reduction in admissions for AMI is beyond the scope of the present work. Nevertheless, recent reports suggested that the decreased number of ACS patients was due to the fear of exposure to COVID-19 affected subjects at hospital admission or a true reduction in the incidence of ACS as the potential result of low physical stress during the social containment [ 6 , 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The identification of the mechanisms leading to the reduction in admissions for AMI is beyond the scope of the present work. Nevertheless, recent reports suggested that the decreased number of ACS patients was due to the fear of exposure to COVID-19 affected subjects at hospital admission or a true reduction in the incidence of ACS as the potential result of low physical stress during the social containment [ 6 , 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Taking into account the frame of the present analysis, meaning early PCI (<2 h) 4 , 5 under clinical conditions in which the adjuvant antiplatelet treatment with oral P2Y 12 inhibitors may not be feasible or desirable, it should also be considered that the antiplatelet effect of crushed ticagrelor 37 and chewed prasugrel 38 were also investigated as potential alternatives to improve their oral bioavailability. Although the results showed that time to maximum plasma concentration was shorter in the crushed ticagrelor group versus the integral tablets group, the median time of 2 h vs 4 h, respectively, still represents the delayed onset of the ticagrelor antiplatelet effect.…”
Section: Discussionmentioning
confidence: 99%
“… 37 In line with these results, the recently published FABOLUS FASTER pharmacodynamic study compared the antiplatelet effect of chewed prasugrel vs a loading dose of integral prasugrel tablet and demonstrated that chewed prasugrel led to higher active metabolite concentration but not to a greater platelet aggregation inhibition. 38 The results of these pharmacodynamic studies emphasize that even the faster oral P2Y 12 alternatives may still not be desirable. In this context, cangrelor represents an affordable iv alternative for immediate P2Y 12 inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…In STEMI patients, randomized data demonstrated that cangrelor may be used as an adjunct to ticagrelor and provides faster and stronger periprocedural platelet inhibition compared with ticagrelor alone (85,86). However in the recent FABOLUS-FASTER trial, tirofiban demonstrated superior efficacy than cangrelor on inhibition of platelet aggregation in patients undergoing primary PCI, suggesting that GPI might be preferable to cangrelor to minimize the risk of acute ischemic complications (87). Further studies powered for clinical endpoints are needed.…”
Section: Accepted Manuscriptmentioning
confidence: 99%